Battle with the Wither - Davidson, Danica (Davidson, Danica. Unofficial Overworld adventure, 2016)
"The terrors of the Nether threaten the Overworld, and it's up to Stevie to restore balance between the Overworld and the Nether, defeat the Wither, and protect his friends and family"--